Analisis Kadar Rhodamin B pada Blush On yang Beredar Via Online Shop Menggunakan Metode KLT dan Spektrofotometri UV-Vis - Putri, Devi Ananda; Qonitah, Fadilah; Ahwan, Ahwan (LPPM, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2024)
Rhodamine B is a synthetic dye used as a paper and textile dye. Rhodamine B is often misused as a dye in cosmetic preparations, one of which is blush on. Long-term use of Rhodamine B in cosmetic preparations will result in cancer and impaired liver function. If exposed to large amounts of Rhodamine B, acute symptoms of poisoning will occur within a short time. This study aims to analyze whether blush on sold through online shops in the Surakarta area contains Rhodamin B. Analysis of Rhodamine B levels used 11 blush on samples purchased through online shops including Shopee, Lazada and Tokopedia. The testing method is carried out with two tests, namely qualitative and quantitative tests. The qualitative test uses Thin Layer Chromatography (TLC) and the quantitative test uses the UV-Vis Spectrophotometry method. Based on the results of research analysis of Rhodamine B levels in blush on sold through online shops in the Surakarta area, of the 11 samples tested, there were 2 blush on samples that were declared positive for containing Rhodamine B, namely sample A and sample C. The respective levels of Rhodamine B in sample A amounted to 797.8 ± 0.92 µg/mL, while sample C was 1,047.20 ± 1.16 µg/mL. In this study it can be concluded that there are 2 blush samples that do not meet the requirements of the Regulation of the Minister of Health of the Republic of Indonesia No.722/Menkes/Per/IX/1998 and the Director General of Drug and Food Control No.00386/C/SK/II/1990.